Human-elephant conflict: the challenge ahead - Kadzo Kangwana (Pachyderm)
Presented as a overview paper at the African Elephant Specialist group meeting in May 1994 the text reflects the contributions of group members, highlights the key issues associated with human-elephant conflict, and suggests that there are policy options which will allow for the migitation of this growing situation as opportunities for conservation management become more fully realised.